TI_GERICHTE 15.2005.99 vom 26. Oktober 2005 , Comminatoria di fallimento. Asserita opposizione. Assenza di prova. - TI Tribunale d'appello (2005)
Comminatoria di fallimento. Asserita opposizione. Assenza di prova.